2018
DOI: 10.3201/eid2406.171585
|View full text |Cite
|
Sign up to set email alerts
|

PathogenicLeptospiraSpecies in Insectivorous Bats, China, 2015

Abstract: PCR amplification of the rrs2 gene indicated that 50% (62/124) of insectivorous bats from eastern China were infected with Leptospira borgpetersenii, L. kirschneri, and several potentially new Leptospira species. Multilocus sequence typing defined 3 novel sequence types in L. kirschneri, suggesting that bats are major carriers of Leptospira.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 12 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…Thus, based on the La Scola et al (2006) recommendations, Grenadian bats harbor several distinct genotypes of Leptospira. Other studies have similarly demonstrated that even within a limited geographical range, bats are often infected with a diverse range of Leptospira [15,19,20] including potentially novel strains [16,43]. However, while the DNA sequences from PCR and phylogenetic analysis merely suggest that bats in Grenada have genetically diverse genotypes, of which several are possibly novel strains, DNA sequences alone are not considered sufficient to classify our unique bat-derived Leptospira genotypes reported herein as novel strains or species.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, based on the La Scola et al (2006) recommendations, Grenadian bats harbor several distinct genotypes of Leptospira. Other studies have similarly demonstrated that even within a limited geographical range, bats are often infected with a diverse range of Leptospira [15,19,20] including potentially novel strains [16,43]. However, while the DNA sequences from PCR and phylogenetic analysis merely suggest that bats in Grenada have genetically diverse genotypes, of which several are possibly novel strains, DNA sequences alone are not considered sufficient to classify our unique bat-derived Leptospira genotypes reported herein as novel strains or species.…”
Section: Discussionmentioning
confidence: 71%
“…Although less resolutive than the phylogenetic analysis with softcore genes, 16S rRNA analysis allows to appreciate the potential diversity that remains to be explored in Leptospira . In this sense, sequences from bats from China [27] clustered among P1 and long lengths of branches of some subclades suggest that some of these strains could correspond to unknown, potentially novel species yet to be isolated. A striking result was the high diversity of sequences recovered from the environment of the Peruvian Amazon and composing the previously named “clade C” [26].…”
Section: Resultsmentioning
confidence: 99%
“…The 16S rRNA sequences of the 66 genomes (including the outgroups), those of strains detected in the environment of the Peruvian Amazon [26] and insectivorous bats from eastern China [27] were aligned and positions of low confidence level masked using SSU-ALIGN version 0.1.1 (http://eddylab.org/software/ssu-align). The best-fit model was determined and a maximum likelihood phylogenetic analysis with 10,000 ultrafast bootstraps was performed with the same tool with IQ-TREE version 1.6.7.…”
Section: Methodsmentioning
confidence: 99%
“…Many mammalian species, including pinnipeds and bats 45,46 , as well as birds, amphibians, and reptiles, are known to carry pathogenic Leptospira species 47,48 . Wild ecosystems, such as those in northern Okinawa, are vastly biodiverse, and several animals may act as potential reservoirs of Leptospira .…”
Section: Discussionmentioning
confidence: 99%